PENGARUH TEMPERATUR ANELING TERHADAP KEKERASAN DAN KEKUATAN PIPA TEMBAGA AC BEKAS - R. N. Akhsanu Takwim; Kris Witono; Pondi Udianto (Universitas Lambung Mangkurat, 2019)
During the installation process, copper pipes for air conditioning will experience a very large deformation due to straightening and bending following the installation path. Hardening strains occur that result in changes in mechanical properties in this case decreases ductility making it difficult to do the connecting process with flaring. Studies need to be carried out to restore the mechanical properties of copper pipes that have been used, including the heat treatment process on copper pipes, so that used copper pipes have a better benefit value than having to be recycled. The temperature of the heat treatment is varied from 400oC, 500 oC and 600 oC. Tensile test results show that at annealed temperature of 400 oC has the highest tensile strength of 125.81 N / mm2 and proportional limit stress of 40.52 N / mm2. Whereas in the microhardness test, the highest hardness occurs also at annealed temperature of 400 oC which is equal to 50.8 HV.